CLEANING METHOD FOR ELECTRIC OR COMMUNICATION RECIEVING FACILITIES USING INSULATING DETERGENT COMPOSITION - KIM, JONG O; KWON, YOUNG CHEOL (2016)
The present invention relates to a method for cleaning electrical or communication storage equipment by using an insulating detergent composition and, more specifically to a cleaning method for removing foreign substances by spraying the same to the electrical or communication storage equipment in the conducting state. The insulating detergent composition comprises: a) 100 to 200 parts by weight of 1,1-dichloroethene; b) 250 to 350 parts by weight of ISOPAR G (EXXON COMPANY); c) 50 to 100 parts by weight of pentafluoroethane; and d) 100 to 200 parts by weight of 1,1,1-2-tetrafluoroethane. 본 발명은 절연 세정제 조성물을 이용한 전기 또는 통신수용설비의 세척방법에 관한 것으로, 보다 구체적으로는 a) 1,1-디클로로에텐 100 내지 200 중량부; b) ISOPAR G(EXXON COMPANY사) 250 내지 350 중량부; c) 펜타플루오로에탄 50 내지 100 중량부; 및 d) 1,1,1,2-테트라플루오로에탄 100 내지 200 중량부가 함유된 절연 세정제 조성물로 통전상태의 전기 또는 통신수용설비에 분사하여 이물질을 제거하는 세척방법에 관한 것이다.